Effects of Utilization of Improved Rice Production Technologies on Productivity among Smallholder Farmers In Niger State - Oduaro, A. O; Olawuyi , T.O; Olatoye, O.C (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
This study examined the level of utilization of improved rice production technologies on productivity among small holder rice farmers in Niger-state, Nigeria. Data were collected on socio-economic characteristics of small holder farmers, accessibility of improved rice technologies, benefits derived productivity of small holder farmers and utilization of improved rice technologies. Using a multistage sampling procedure, 120 respondents were sampled and data was obtained with the aid of questionnaire and interview schedule. Descriptive and inferential statistics were used to analyzed data. Results showed that majority of the respondents were in their productive age with an average age of 37 years. Majority, (86.7%) were married, most (99.2%) were Muslims while most (66.7%) of the respondents had access to improved rice technologies. The study also revealed that (78.3%) utilized the improved rice technologies, (85%) derived high benefits and (78.3%) had high level of productivity. There is a significant relationship between utilization of improved rice technologies and productivity r = (0.721; P 0.000). The study recommends that farmers need continuous access to improved rice technologies to boost their productivity. There is also a need for government and stakeholders to provide adequate training to smallholder farmers on the use of improved rice technologies for more productivity.